Pemanfaatan Moodle pada Identifikasi Kendala dalam Soal Reading dengan Format Tes TOEIC - Aji, Satriya Bayu; Antoni, Condra (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2019)
Most TOEIC test takers who score low are unfamiliar with the format of the test. This study aims to identify the problems that will likely become obstacles in the Reading Section of the TOEIC test. The data come from the results of the English I online final exam in the second term of 2017/2018 as well as the English II online mid-term and final exam in the first term of 2018/2019, all of which were held in Politeknik Negeri Batam. The exams are part of Moodle-based e-learning courses. The data consist of questions which have a low percentage of correct answers. The analysis was done by classifying the questions based on the five abilities measured in the Reading Section (vocabulary, grammar, specific information, inference, and connection). Based on the analysis, it can be observed that the biggest challenge comes from grammar, while the search for specific information poses little to no problem at all. It means the students still consider Reading Section of TOEIC test requires no special attention.